A method of regulating the wind field to reduce safety hazards of gas and dust in fully mechanized heading face based on dynamic data. Issue 11 (November 2022) - Liu, Zhuangzhuang; Gong, Xiaoyan; Chen, Long; Wei, Minjie; Cheng, Ao; Wu, Yue; Han, Zheng; Xue, He; Niu, Huming; Li, Hao
Abstract: Accumulation of gas and dust in excavation work is a safety risk that remains to be solved. A substantial amount of gas and dust accumulate in fully mechanized heading face outlets, and the press-in tube jet cannot be adjusted dynamically based on the actual physical conditions. To solve the problem, a dynamic data-driven method for optimising gas and dust distribution by regulating the wind field is proposed. This method is based on the immune genetic algorithm and uses dynamic data as the incremental data with the historical data from the mine regulation rules to obtain the optimal incremental regulation rules (IRRs) for the wind field. The experiment was performed in Ningtiaota coal mine, Yulin city, northern Shaanxi, China. The observed wind velocity and gas concentrations were within the specification range when regulated by IRRs. The dust concentrations at the position of the driver and the average concentrations on the return air side decreased by 64.6 % and 56.5 %, respectively, when the outlet was 5 m from the head-on. When the distance of the outlet from the head-on was 10 m, the dust concentrations at the position of the driver and the average concentrations on the return air side dropped by 42.9 % and 68.6 %, respectively. The results from this study provide measures that would improve safety and efficiency during excavation of fully mechanized heading faces. Abstract : Fully mechanized heading face; Gas and dust measurements; Immune genetic algorithm; Incremental regulation rules for wind fields.